A photoactive porous metal–organic complex: synthesis, crystal morphology and the influence of photocycloaddition on fluorescence properties and adsorption behavior1. Issue 11 (21st March 2015) - Cai, Li-Xuan; Chen, Cheng; Tan, Bin; Zhang, Ya-Jun; Yang, Xiao-Dong; Zhang, Jie
<x xml:space="preserve">Abstract</x> An olefin-containing pyridinium-based complex stabilized by cation–π interactions undergoes photoinduced [2 + 2] cycloaddition, accompanied by turn-on fluorescence.